FRB event rate counts – II. Fluence, redshift, and dispersion measure distributions. Issue 3 (2nd August 2018) - Macquart, J-P; Ekers, RD
ABSTRACT: We examine how the various observable statistical properties of the fast radio burst (FRB) population relate back to their fundamental physical properties in a model-independent manner. We analyse the flux density and fluence distributions of FRBs as a tool to investigate their luminosity distance distribution and the evolution of their prevalence throughout cosmic history. We examine in detail particular scenarios in which the burst population follows some power of the cosmic star formation rate. FRBs present an important additional measurable over source counts of existing cosmological populations, namely the dispersion measure. Based on the known redshift of FRB121102 (the repeater) we expect at least 50 per cent of the dispersion measure to be attributable to the intergalactic medium and hence it can be used as a proxy for distance. We develop the framework to interpret the dispersion measure distribution, and investigate how the effect of Helium reionization in the intergalactic medium is evident in this distribution. Examination of existing data suggests that the FRB luminosity function is flatter than a critical slope, making FRBs easily detectable to large distances; in this regime the reduction in flux density with distance is outweighed by the increase in the number of bright bursts within the search volume.